Kekuatan Modal Sosial dan Keberhasilan Gerakan Sayang Ibu (Belajar dari Pengalaman Gampong Tibang–Kota Banda Aceh Dalam Mengupayakan Persalinan Aman Bagi Ibu Hamil) - Masrizal Masrizal (Jurnal Community, 2016)
This paper describes how Gampong Tibang, a coastal settlement severely damaged by the tsunami in 2004 with programs Loving Mother Movement (GSI) is integrated between the community and the government in improving the quality of life of women with a variety of activities having an impact on efforts to reduce mortality mothers due to pregnancy, childbirth, and the postpartum and infant mortality rate in view of the cases are still found in society. The approach in this study is qualitative with data collection techniques through observation, interviews, focus group discussions, and documentation. The findings of this research is the GSI program implemented by the government of the city of Banda Aceh, through the Department of Health in this regard by training cadres Posyandu health centers as a key actor village level. The program aims to address a variety of health problems experienced by pregnant mothers, giving stimulants to family and society and thus creating a more hospitable environment for pregnant and lactating mothers. The approach used is to improve the understanding of the family and the community through mentoring and counseling activities and create the environment conscious, responsive and able to prevent and overcome the various problems faced by pregnant women to exploit the potential of the local community. Residents are also trained to be ready under any circumstances stand to give first aid for pregnant women. For this purpose, a series of activities such as data collection pregnant women do and then to pregnant mothers are given identification card/specific reference to the condition of the pregnant mother so that people can easily know it. Likewise, for the people who have volunteered their car as "ambulance village" that used to transport pregnant women to the hospital/clinic or to the other treatment when undergoing the process of childbirth. To ease the labor process, labor costs to be repaid through Tabungan Ibu Bersalin (Tabulin). If there are people who have not been able to repay will be bailed out. Bailed out funds was taken from the Tabulin of other mothers. The pregnant women in the village were examined periodically by a midwife. The program is also reinforced with a variety of other activities to support the safe delivery for mothers with community-based (local wisdom). Keyword: Loving Mother Movement, Local Wisdom, Social Capital